Comparative Evaluation of Occupational Safety and Health Management System (OSH-MS) Practices in Power Plant, HSR, and NAM Industries - Herlina J. EL-Matury; Nabila Syahlan; Mohd Rafee B. Baharuddin (Jurnal Kesehatan dan Keselamatan Kerja Universitas Halu Oleo, 2026)
Occupational Health and Safety (OHS) management is essential for ensuring workplace safety and sustaining organizational operations, particularly in industries with varying levels of risk. Inadequate implementation of OHS management systems can result in workplace accidents, occupational diseases, operational disruptions, and economic losses. This study aims to evaluate and compare the implementation of OHS management practices across three companies from different industrial sectors: a Power Plant, HSR, and NAM. A quantitative descriptive-comparative research design was employed. Each company provided five informants directly involved in OHS management, including the OHS Manager, OHS Coordinator, Safety Officer, and Administrator, for a total of fifteen informants. Data were collected using structured checklist instruments and document reviews based on five core principles of OHS management: policy establishment, planning, plan implementation, performance monitoring and evaluation, and review and continuous improvement. Compliance levels were analyzed descriptively and presented as percentages for comparison across companies. The results indicate that the Power Plant achieved the highest compliance, particularly in policy, systematic planning, and structured monitoring and evaluation. HSR showed moderate compliance, with gaps in planning and performance evaluation. NAM demonstrated the lowest compliance, especially in planning (14%) and performance review and improvement (17%), highlighting critical areas requiring immediate attention. Based on these findings, this study recommends strengthening risk-based OHS planning, enhancing staff competencies through continuous training, and implementing regular internal audits and management reviews. Sector-specific strategies are essential to improve the effectiveness of OHS management systems and sustainably reduce workplace accident risks.